Messianismo e neopentecostalismo: uma análise da práxis religiosa de Valdemiro Santiago da Igreja Mundial do Poder de Deus - Zanini, André Luis (2009)
The aim of this work is a reflection about messianism and neopentecostalism. Among neopentecostals leaders, Apostle Valdemiro Santiago was chosen as a former bishop of Igreja Universal do Reino de Deus. But he is now the founder of Igreja Mundial do Poder de Deus. This church appears as a new hope for many people in the Brazilian religious field. The Apostle has a significant prestige among believers. They usually want to touch him because they believe power and virtue exhale from him including from his own sweat. Which means, that: Valdemiro is a charismatic neopentecostal minister who shows messianic traces. The focus of this work is to comprehend the messianic traces in Valdemiros Santiago in religious praxis and its relation with the major diffusion of Igreja Mundial do Poder de Deus. It is crucial to comprehend that messianism, according to Henry Desroche, is based upon hope. In Neopentecostalism, as in Igreja Mundial do Poder de Deus, there is a straight correlation between financial prosperity as the representation of the divine force, which mobilizes the believer to act in benefit of its conquest. This work approaches some of the most significant images concerning God due to religious praxis found in the referred institution.